2006
DOI: 10.1101/lm.241006
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval failure versus memory loss in experimental amnesia: Definitions and processes

Abstract: For at least 40 years, there has been a recurring argument concerning the nature of experimental amnesia, with one side arguing that amnesic treatments interfere with the formation of enduring memories and the other side arguing that these treatments interfere with the expression of memories that were effectively encoded. The argument appears to stem from a combination of (1) unclear definitions and (2) real differences in the theoretical vantages that underlie the interpretation of relevant data. Here we spea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
51
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 64 publications
1
51
0
1
Order By: Relevance
“…Below we examine a number of similar recovery e ects that have been observed in studies where amnesia is induced through brain injury or invasive interventions such as ECS and PSIs (for review see Lewis & Maher, 1965;R. R. Miller & Springer, 1973;R. R. Miller & Matzel, 2006;Riccio & Richardson, 1984;Spear, 1973 Brown, 2002;Squire & Alvarez, 1995).…”
Section: Recovery From Experimentally-induced Amnesiamentioning
confidence: 99%
“…Below we examine a number of similar recovery e ects that have been observed in studies where amnesia is induced through brain injury or invasive interventions such as ECS and PSIs (for review see Lewis & Maher, 1965;R. R. Miller & Springer, 1973;R. R. Miller & Matzel, 2006;Riccio & Richardson, 1984;Spear, 1973 Brown, 2002;Squire & Alvarez, 1995).…”
Section: Recovery From Experimentally-induced Amnesiamentioning
confidence: 99%
“…Also, as in other areas of memory research (e.g., experimental amnesia 35 ), studies of HIV-related memory impairment have varied significantly in the operational definitions and semantic labels used for various memory-process deficits. To reduce any potential confusion in this regard, in the present study and discussion, we used a three-stage/process model of episodic memory: 36 the first process being encoding, where information is taken in and transformed into a format that can be stored in the brain; the second stage is consolidation, where the transformed information is stored in the brain for later use; the third is retrieval, or extraction of the stored information for use.…”
mentioning
confidence: 99%
“…However, from the perspective of the aforementioned storage-retrieval debate (18), this interpretation should be viewed with caution, especially as retrieval deficit explanations were not explored. For example, it was not clear whether the effect endured beyond the 3-day study period, or showed propensity for recovery under favorable retrieval conditions (26), effects that have been observed in several investigations of reconsolidation with nonhuman animals (e.g., refs.…”
mentioning
confidence: 99%
“…It is worth noting that the reconsolidation controversy is only the latest chapter in an enduring historical debate about the locus of interference and forgetting effects (18). On the one hand, amnesia for previously recallable information has been attributed to storage deficits: the permanent physical modification of memory traces by postencoding and postretrieval interventions [e.g., "consolidation" (19); "unlearning" (20); "destructive updating" (21); "reconsolidation" (2)].…”
mentioning
confidence: 99%